2004
DOI: 10.1080/02699050410001671847
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of a cube-copying test in outpatients with dementia

Abstract: The cube-copying test is useful for routine clinical dementia screening, however the test examines only one aspect of cognitive function. While not an alternative to conventional neuropsychological examinations, quantitatively scored cube copying can provide a rough estimate of cognitive dysfunction in dementia patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 9 publications
0
34
0
Order By: Relevance
“…Each plane with two pairs of parallel lines was evaluated in terms of the number of lines and the extent to which they were parallel. No plane-error points were scored if the cube was copied accurately [20]. We selected brief neuropsychological tests that could be performed within 1 h in order to reduce the burden on patients in the preoperative or postoperative therapeutic stage.…”
Section: Methodsmentioning
confidence: 99%
“…Each plane with two pairs of parallel lines was evaluated in terms of the number of lines and the extent to which they were parallel. No plane-error points were scored if the cube was copied accurately [20]. We selected brief neuropsychological tests that could be performed within 1 h in order to reduce the burden on patients in the preoperative or postoperative therapeutic stage.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the applied 20-point scoring system of the cube copying test enables the detection of minor deficits of the visuospatial functions. Maeshima et al [9] have previously shown that this test can distinguish controls from AD subjects. However, to our knowledge, no previous study has investigated this assessment of the cube copying test in the prediction of AD in MCI subjects.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the cube copying test in a quantitative manner, Maeshima et al [8] developed a rating scale of 20 points. Using this scale, patients with established AD could be separated from healthy controls [9] . However, such an extensive rating scale of the cube copying test has not been evaluated in the detection of preclinical AD.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, DLB patients as well as AD patients often show poor performances in cube or clock copying tests [17][18][19][20] , because of the difficulty for dementia patients to copy these designs. The Rey-Osterrieth complex figure test has not been examined in DLB patients but leads to poor performances in AD patients [21] .…”
Section: Introductionmentioning
confidence: 99%